The effectiveness of MALL and flipped classroom in teaching writing to the eleventh graders of SMA in Banyumas - Benny Krisbiantoro; Tri Pujiani (Universitas Islam Sultan Agung, 2021)
MALL has become an invaluable means in teaching writing for learners in and out of the classroom. Although there were many researches on MALL to enhance writing competence, analytical exposition text writing was never carried out. This study was aimed to investigate whether: (1) MALL was more effective than Flipped classroom to teach writing for the eleventh graders of SMA (senior high school); (2) the high creative students possessed better writing skills than the low creative ones; and (3) an interaction effect occurred between the methods of teaching and creativity to teach writing for the eleventh graders of SMA in Banyumas. The employed method was an experimental research with factorial design. The population of the research was the eleventh graders of SMA in Banyumas. Four schools were purposively taken. There were two samples in this research; experimental class comprising 72 students from SMAN 01 Banyumas and SMAN 01 Baturraden and control class containing 72 students from SMAN 03 Purwokerto and SMAN 01 Sokaraja. The occupied instruments in this research were verbal creativity and writing test. The data analyses were in the matter of frequency distribution, normality, homogeneity, ANOVA and TUKEY. The results of the study revealed that: (1) MALL is more effective than Flipped classroom in teaching writing for the eleventh graders of SMA; (2) the high creative students possessed better writing competence than the low creative students; and (3) an interaction effect happened between the methods of teaching and creativity in regards to writing teaching.